Impacto da qualidade da matéria-prima no processo de refino de óleos vegetais - Valle, Gabrielle Alves do; Araújo, Júlia Carvalho (Universidade Federal de São Carlos, 2025)
The vegetable oil industry in Brazil began to develop in the 1950s, driven by the growth of agricultural production. Over time, technological advances improved oil quality, making it popular in food consumption and establishing the sector as an essential part of the national food industry. This study aims to investigate the impact of raw material quality on the refining process of vegetable oils, with an emphasis on a case study involving canola oil refining. Initially, a bibliographic review was conducted, covering the historical overview of the sector, production and consumption statistics, main raw materials (soybean, canola, corn, and sunflower), the chemical composition of crude oils, and the stages of extraction processes (mechanical pressing and solvent extraction) and refining (chemical and physical). The influence of parameters such as acidity, moisture, the presence of metallic impurities and phosphatides, as well as the peroxide index, on refining efficiency and yield was highlighted. The challenges of balancing the removal of undesirable components (free fatty acids, pigments, gums, and metals) with the preservation of nutritional compounds (tocopherols, phytosterols, and carotenoids) during the deodorization and bleaching stages were also discussed. The case study was conducted in a refinery, comparing two production campaigns. It was observed that higher-quality raw material resulted in lower consumption of inputs, elimination of reprocessing, higher yield, and increased operational efficiency. The results reinforce the importance of strict quality control of raw materials, from reception to storage, as a decisive factor for the final product quality and the sustainability of the industrial process. Keywords: Process efficiency, crude oil, quality, canola oil.
Impact of raw material quality on the vegetable oil refining process
Keywords: Eficiência do processo; Óleo bruto; Qualidade; Óleo de canola; Process efficiency; Crude oil; Quality; Canola oil; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS; 9. Indústria, Inovação e Infraestrutura